Resisting self-compassion: Why are some people opposed to being kind to themselves?. Issue 5 (2nd September 2016) - Robinson, Kelley J.; Mayer, Selina; Allen, Ashley Batts; Terry, Meredith; Chilton, Ashley; Leary, Mark R.
Abstract: Although self-compassion is associated with positive emotions, resilience, and well-being, some people resist recommendations to treat themselves with kindness and compassion. This study investigated how people's personal values and evaluations of self-compassionate behaviors relate to their level of self-compassion. After completing measures of trait self-compassion and values, participants rated how they would view themselves after behaving in a self-compassionate and self-critical way. Overall, participants associated self-compassion with positive attributes that connote emotional well-being, yet only those who were low in trait self-compassion associated self-compassionate responding with negative attributes that involve low motivation, self-indulgence, low conscientiousness, and poor performance. Participants' endorsement of basic values was not meaningfully related to their evaluations of self-compassionate vs. self-critical behaviors or to self-compassion scores. We propose that self-compassion might operate as an instrumental value insofar as those high vs. low in self-compassion differ in their beliefs about whether self-compassion affects performance-related outcomes positively or negatively.